IttiḥᾹd Al-Majlis on Marriage Contract According to Hanafiyah and Syafi'iyah (The Study of Online Marriage During Covid-19): Nikah Online - Harahap, Khairuddin Soleh; Qorib, Ahmad; Yazid, Imam (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
Ittiḥād al-majlis is one of the terms in the discussion of the marriage contract. Hanafiyah and Syafi’iyah differ in the ittiḥād al-majlis. This disference has implications for its application in implementation of online marriage contracts during the covid-19 pandemic. Analysis of the methodology for determining the law is important to study because there has been an online marriage in the city of Medan during the Covid-19 outbreak. This paper aims to explain how the rules of the Hanafiyah and Syafi’iyah schools in understanding ittiḥād al-majlis, and how the law of online marriage during the Covid-19 pandemic according to Hanafiyah and Syafi’iyah. This paper is a normative legal study, which examines the legal rules applied in the Hanafiyah and Syafi’iyah schools. The theory of ushul fiqh, namely how the rules are applied by these two schools to determine the meaning of a word. This study found that: First, Hanafiyah and Syafi’iyah have strong argument in giving the meaning of the majlis. Second, Hanafiyah interprets majlis as a word that indicates time, so that the unity of the place is not a condition for the validity of the marriage contract. As for Syafi’iyah, majlis is a word that indicates time and place, so the marriage contract must be in one place, where if the unity of the place is not fulfilled, then the marriage is invalid